2013
DOI: 10.5195/ijt.2013.6129
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Costs and Outcomes of Tele-Intervention When Serving Families of Children who are Deaf/Hard-of-Hearing

Abstract: Background:Optimal outcomes for children who are deaf/hard-of-hearing (DHH) depend on access to high quality, specialized early intervention services. Tele-intervention (TI), the delivery of early intervention services via telehealth technology, has the potential to meet this need in a cost-effective manner.Method:Twenty-seven families of infants and toddlers with varying degrees of hearing loss participated in a randomized study, receiving their services primarily through TI or via traditional in-person home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 10 publications
9
61
0
Order By: Relevance
“…We used home‐visiting quality ratings to observe home‐visiting quality in EHS, but these quality ratings have been used for other home‐visiting programs using a similar approach (e.g., Boyce et al., ), and a version of the measure also has been used to measure home‐visiting quality in early intervention in both face‐to‐face and tele‐intervention home visits (Blaiser, Behl, Callow‐Heusser, & White, ). The practices measured by our home‐visiting practices ratings could be enhanced with training or coaching, just as similar practices have been increased with training in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…We used home‐visiting quality ratings to observe home‐visiting quality in EHS, but these quality ratings have been used for other home‐visiting programs using a similar approach (e.g., Boyce et al., ), and a version of the measure also has been used to measure home‐visiting quality in early intervention in both face‐to‐face and tele‐intervention home visits (Blaiser, Behl, Callow‐Heusser, & White, ). The practices measured by our home‐visiting practices ratings could be enhanced with training or coaching, just as similar practices have been increased with training in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited literature to clarify the comparison of costs between telemodels and in-person models for service delivery. A study including children with hearing loss who underwent teleintervention in Utah, USA, reported costsavings between USD 56,280 and USD 6,970 compared with the in-person intervention over a 24-month period (Blaiser et al, 2013). Ramkumar et al (2018), reported the cost outcomes of community-based hearing screening programs integrated with remote diagnostic ABR via tele-audiology.…”
Section: Cost Outcomes Of Tele-audiological and In-person Audiologicamentioning
confidence: 99%
“…In the teleintervention model of practice, EI providers are required to improve their communication and modelling skills so parents become fully engaged and confi dent in the recommended O&M strategies. Research from various teleintervention models demonstrated an increased use of the family-centered coaching model of intervention (Blaiser, Behl, Callow-Heusser, & White, 2013;Heimerl & Rasch, 2009;Kelso et al, 2009;Olson et al, 2012). In a randomised controlled trial that compared EI teleintervention services to EI in-person services parent engagement was statistically more signifi cant (p < .05) for families receiving EI teleintervention (Blaiser et al, 2013).…”
Section: A Preview Of the Teleintervention Modelmentioning
confidence: 99%
“…Research from various teleintervention models demonstrated an increased use of the family-centered coaching model of intervention (Blaiser, Behl, Callow-Heusser, & White, 2013;Heimerl & Rasch, 2009;Kelso et al, 2009;Olson et al, 2012). In a randomised controlled trial that compared EI teleintervention services to EI in-person services parent engagement was statistically more signifi cant (p < .05) for families receiving EI teleintervention (Blaiser et al, 2013). The necessity of using coaching strategies with parents through an EI teleintervention model suggests an opportunity to promote family-centred best practices to increase parent engagement and positive child outcomes.…”
Section: A Preview Of the Teleintervention Modelmentioning
confidence: 99%